PERAN PEMERINTAH DALAM MEMBERANTAS TERORISME - Edi Saputra Hasibuan (Jurnal Kajian Ilmu Kepolisian dan Anti Korupsi, 2024)
Radicalism and terrorism have created a national security crisis, especially in the current digital era. The era of digitalization has given birth to rapid changes and has had massive effects in various sectors, including the movement of new forms of terrorism. Terrorist groups have changed movement patterns by utilizing the internet, from spreading ideology, recruiting, funding, exchanging information and terror threats. The Internet enables rapid, low-risk, and inexpensive dissemination of information to diverse constituencies. Therefore, appropriate measures are needed to prevent terrorism. However, the implementation of digitalization-based terrorism prevention is currently unable to be realized effectively. If we look at it, since the September 11 2001 terrorist attack on the World Trade Center (WTC), terrorism has become an issue that has been widely discussed in all parts of the world. Almost all countries agree to fight terrorism, because terrorism is contrary to humanitarianism and has caused economic, political and psychological losses.  This research analyzes the government's role in eradicating terrorism in the era of digitalization. It is hoped that this research can contribute to scientific development related to handling terrorism in Indonesia. The aim of the study is to describe the causal factors and formulate steps taken by the government to overcome radicalism and terrorism in Indonesia.